THE EVOLUTION OF CHINESE JINGDEZHEN IN THE BLUE AND WHITE PORCELAIN - HeYingJie; Khairun Nisa Mustaffa Halabi (Journal of Islamic, Social, Economics and Development, 2024)
The study explores the fascinating journey of Chinese Jingdezhen porcelain, particularly focusing on its transformation in the context of blue and white ceramics. Over centuries, Jingdezhen has been a renowned center for porcelain production, and blue and white porcelain has held a significant place within this tradition. This research endeavors to trace the evolution of blue and white porcelain in Jingdezhen, shedding light on the intricate development, techniques, and artistic influences that have shaped this unique art form. To comprehensively understand the evolution of blue and white porcelain in Jingdezhen, a quantitative approach will be employed. This will involve collecting and analyzing historical production data, including the quantity and types of blue and white porcelain produced over different periods. Statistical methods will be used to identify trends, production peaks, and changes in design preferences. Data will be sourced from historical records, archaeological findings, and museum collections. This study aims to provide a comprehensive understanding of the evolution of Chinese Jingdezhen blue and white porcelain. By combining quantitative and qualitative analyses, we will uncover the historical, artistic, and cultural factors that have contributed to the development of this exquisite porcelain tradition. The findings will offer insights into the changing tastes, production techniques, and cultural significance of blue and white porcelain in Jingdezhen over time. Ultimately, this research seeks to contribute to a deeper appreciation and knowledge of one of China's most treasured artistic legacies.